2002
DOI: 10.1093/ajcn/76.2.436
|View full text |Cite
|
Sign up to set email alerts
|

Impaired functioning of thermolabile methylenetetrahydrofolate reductase is dependent on riboflavin status: implications for riboflavin requirements

Abstract: The high tHcy concentration typically associated with homozygosity for the 677C-->T variant of MTHFR occurs only with poor riboflavin status. This may have important implications for governments considering new fortification policies aimed at the prevention of diseases for which this genotype is associated with increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 29 publications
2
91
0
Order By: Relevance
“…This response was not observed in individuals with CC or CT genotypes (even when baseline riboflavin status was suboptimal) despite a significant improvement in riboflavin status post-intervention in both genotype groups. Such evidence confirmed the independent modulating role of riboflavin in determining homocysteine concentrations specifically in individuals with the TT genotype as first suggested by earlier observational studies (18,19) .…”
Section: Proceedings Of the Nutrition Societysupporting
confidence: 88%
“…This response was not observed in individuals with CC or CT genotypes (even when baseline riboflavin status was suboptimal) despite a significant improvement in riboflavin status post-intervention in both genotype groups. Such evidence confirmed the independent modulating role of riboflavin in determining homocysteine concentrations specifically in individuals with the TT genotype as first suggested by earlier observational studies (18,19) .…”
Section: Proceedings Of the Nutrition Societysupporting
confidence: 88%
“…An earlier animal study showed a significant association between vitamin B 2 and MTHFR that the enzyme activity and the relative amounts of 5-methyl THF were reduced in the liver of riboflavin-deficient rats (Bates & Fuller, 1986). Hustad et al (2000), McNulty et al (2002), and Jacques et al (2002) demonstrated that plasma vitamin B 2 was an independent determinant of plasma homocysteine, and this inverse dose-response relation was essentially confined to subjects with the C/T or T/T genotype of the MTHFR C677T polymorphism where the requirement of FAD for maximal catalytic activity might be increased (Hustad et al, 2000;Ueland et al, 2001). Several investigators have suggested that vitamin B 6 deficiency may lead to hyperhomocysteinemia, which is an established risk factor for adverse pregnancy outcome (van den Berg et al, 1994;Leeda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that riboflavin, the precursor for flavin adenine dinucleotide, might act by increasing MTHFR activity, and thereby lower plasma tHcy concentrations (Bates and Fuller, 1986;Ross and Hansen, 1992;McNulty et al, 2002). Examining the effects of folic acid, riboflavin, and the MTHFR genotype on human lymphocytes grown in culture media, Kimura et al (2004) observed that the tHcy concentration decreased as the riboflavin concentration increased.…”
Section: Introductionmentioning
confidence: 99%